2017
DOI: 10.1016/j.drugalcdep.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related cognitions in children (aged 2–10) and how they are shaped by parental alcohol use: A systematic review

Abstract: Research on children's alcohol-related cognitions is underdeveloped. To elucidate the conclusions about alcohol involvement in early life, studies with longitudinal study designs need to be conducted among representative samples of children and early adolescents by using age-appropriate measurement tools in a broader cultural context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
0
33
1
3
Order By: Relevance
“…This is important because, as argued by Voogt et al . (2017) , some parents may drink frequently, but not when their children are present, and others may drink less frequently but may predominantly do so in front of their children. This suggests that children's exposure to parental alcohol use rather than parental alcohol use per se, may be more important to role modelling.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because, as argued by Voogt et al . (2017) , some parents may drink frequently, but not when their children are present, and others may drink less frequently but may predominantly do so in front of their children. This suggests that children's exposure to parental alcohol use rather than parental alcohol use per se, may be more important to role modelling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are differences in associations between parental alcohol use and offspring AE by gender of the offspring. Two studies among early adolescents in the United States and among 3‐ to 6‐year‐olds in Switzerland showed that paternal alcohol use was associated with AE for sons, but not for daughters (Handley and Chassin, ; Kuntsche and Kuntsche, ), whereas the opposite was found among 6‐ to 9‐year‐olds in the Netherlands (Mares et al., ; Voogt et al., ). Considering these mixed findings of parental alcohol use and AE among boys and girls, we tested the hypotheses for the full sample and separately by gender, but we did not formulate any gender‐specific hypotheses.…”
Section: Hypothesesmentioning
confidence: 99%
“…Alcohol expectancies (AE) are defined as the anticipated positive or negative effects of consuming alcohol (Jones et al., ). Evidence suggests that AE develop years before the first alcohol consumption (Jester et al., ; Kuntsche, ; Voogt et al., ) and that they are important determinants of alcohol‐related behavior later on (Campbell and Oei, ; Donovan, ; Smit et al., ). To illustrate, 1 longitudinal study found that positive AE among 6‐ to 8‐year‐olds predicted alcohol initiation and binge drinking (i.e., drinking 5 or more glasses of standard alcohol units on 1 drinking occasion [Wechsler and Nelson, ]) even 9 years later (Jester et al., ).…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations